Exploring Elementary Students’ Learning Experiences through Busy Book Media - Henti Sulistiowati; Sholeh Hidayat; Nurul Anriani (JURNAL INOVASI PENDIDIKAN DAN SAINS, 2026)
Learning experiences are essential in shaping students' thinking abilities, attitudes, and motivation. At the elementary level, effective teaching must position students as active participants who construct knowledge through direct experience. From a constructivist perspective, knowledge is actively built through interaction, exploration, and reflection within meaningful learning environments. This study aims to describe and analyze the learning experiences of elementary school students engaged in constructivist-based learning using Busy Book as an instructional medium. A descriptive qualitative approach was used, involving observations, interviews, and documentation with 29 second-grade students and one classroom teacher. The findings showed that Busy Book promoted active engagement, increased self-confidence, and developed students' speaking skills, creativity, and collaborative abilities. The manipulative and exploratory nature of the Busy Book allowed students to understand abstract concepts concretely while fostering reflective thinking. The teacher acted as a facilitator, guiding students to construct understanding through meaningful experiences. In conclusion, the study demonstrates that Busy Book effectively supports the application of constructivist learning principles in line with the Merdeka Curriculum and serves as a creative medium for active, collaborative, and engaging learning in elementary education